Passivation of recombination active PdSex centers in (001)-textured photoactive WSe2 films. (April 2019) - Bozheyev, Farabi; Rengachari, Mythili; Berglund, Sean P.; Abou-Ras, Daniel; Ellmer, Klaus
Abstract: Highly (001)-textured tungsten diselenide WSe2 thin films are crystallized from X-ray amorphous WSex films with Pd-promotion in an H2 Se atmosphere. During the crystallization process, the liquid promoter PdSex is driven to the grain boundaries due to the lateral growth of WSe2 platelets and their coalescence. The photoactivity of the WSe2 films is limited by the PdSex crystallites at the grain boundaries of WSe2 platelets. The presence of the PdSex crystallites leads to a metal like behavior of the conductivity versus temperature, whereas their etching leads to a semiconducting behavior of the WSe2 film. After selective etching of these crystallites, the more active WSe2 sites (edges, cavities) are exposed, enhancing the electron transfer to the electrolyte. A photocurrent density of 2 mA cm −2 at 0.35 V vs. reversible hydrogen electrode (RHE) is observed in sulfuric acid (0.5 M H2 SO4 ) using Fe 2+ /Fe 3+ as redox pair under 1 sun (Air Mass (AM) 1.5, 100 mW cm −2 ) illumination.